Trauma, guilt and reparation the path from impasse to development - Weiss, Heinz 1955- (Routledge, 2020)
"Trauma, Guilt and Reparation identifies the emotional barriers faced by people who have experienced severe trauma, as well as the emergence of reparative processes which pave the way from impasse to development. The book explores the issue of trauma with particular reference to issues of reparation and guilt. Referencing the original work of Klein and others, it examines how feelings of persistent guilt work to foil attempts at reparation, locking trauma deep within the psyche. It provides a theoretical understanding of the interplay between of feelings of neediness with those of fear, wrath, shame and guilt, and offers a route for patients to experience the mourning and forgiveness necessary to come to terms with their own trauma. The book includes a Foreword by John Steiner. Illustrated by clinical examples throughout, it is written by an author whose empathy and experience make him an expert in the field. The book will be of great interest to psychotherapists, social workers and any professional working with traumatized individuals"--